VOLTINI
Rozwiązane

Wykaż, że dla x ≠ 7, wartością wyrażenia [tex]\frac{x^{2}-2\sqrt{7}x+7 }{x-\sqrt{7} }* (x+\sqrt{7})-x^{2}+14[/tex] jest 7



Odpowiedź :

Odpowiedź:

(x² - 2√7x + 7)/(x - √7) * (x + √7) - x² + 14

założenie:

x - √7 ≠ 0

x ≠ √7

D: x ∈ R - {√7}

(x² - 2√7x + 7)/(x - √7) * (x + √7) - x² + 14 =

= (x - √7)²/(x - √7) * (x + √7) - x² + 14 = (x - √7)(x + √7) - x² + 14 =

= x² - 7 - x² + 14 = 7 c.n.u

[tex]\dfrac{x^2-2\sqrt7+7}{x-\sqrt7}\cdot(x+\sqrt 7)-x^2+14=\\\\\dfrac{(x-\sqrt7)^2}{x-\sqrt7}\cdot(x+\sqrt 7)-x^2+14=\\\\(x-\sqrt7)(x+\sqrt7)-x^2+14=\\x^2-7-x^2+14=\\7[/tex]